PENGARUH SUBSTITUSI TEPUNG LABU KUNING DENGAN TEPUNG AGAR TERHADAP SIFAT FISIK, KIMIA, DAN SENSORIS PUMPKIN BAR - , FAJAR HARDIANTORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pumpkin is a local comodity that can be processed into pumpkin flour and to be used to substitute wheatflour utilization of wheat flour in baking products. Addition of agar flour increased the fiber content but might affect the properties of the product. The aim of the research were to determine the optimum substitution pumpkin flour with agar powder on the sensoric, physical, and chemical properties of the pumpkin bar. Variation of the substitution were 5, 10 and 15 %, respectively with the control of 0%. The chemical analysis consists of moisture, ash, protein, lipid, carbohydrate were determined with AOAC methode, dietary fiber was analyzed with gravimetric methode. Atrribute difference test was used to determine the sensoric properties of the pumpkin bar. The result showed that pumpkin bar with 15% agar substitution gave the most similar physical attribute compared to commercial food bar. The water, ash, protein, and lipid content of pumpkin bar with 15% agar substitution were lower than pumpkin bar control, but have higher carbohydrate. The hardness of the pumpkin bar also increased with the substitution of 15% agar powder. This Product has a higher dietary fiber content (17,88%) compared to the control Food Bar (11,45%).